EFFECT OF HEN EGG LYSOZYME ON PROTEIN CONTENT AND ACID PHOSPHATASE ACTIVITY PROFILE OF ANTHERAEA MYLITTA DRURY - MUSARRAT NAAZ,; DR. ABHIJIT DUTTA,; ABHA PRASAD, (International Journal of Pharma and Bio Sciences, 2014)
Tropical tasar silkworm, Antheraea mylitta Drury DABA-ecorace is commercially exploited in India for tasar silk production. Generally, its cocoons get infected with different microbes which causes loss to the silk industry. To curb these diseases antibiotics are being used but with partial success. In the present study, an antimicrobial peptide, Hen egg lysozyme (HEL) has been used and enzyme-based methods have been used to evaluate the impact on A. mylitta pupae. Interestingly, differences in protein concentration and fat body acid phosphatase (Acp) activity of treated pupae have been observed. Significant variation was observed in both profileof control and treated male pupae.The protein content of treated pupa has been found to be more than untreated but Acp activity profile have found decreased in treated pupae. It is expected that, based on protein content and enzyme-based method impact of antimicrobial peptideson A.mylitta pupae can be evaluated/observed and different antimicrobial peptides can be used as alternative to antibiotics resulting in increased silk yield.